Values Education in Curriculum Reform: A Qualitative Document Analysis of the Türkiye Century Maarif Model for Primary Education - Ethem Gürhan (Journal of Educational Research and Practice, 2026)
Values education has become a central concern in contemporary curriculum reforms as education systems seek to balance academic achievement with character and moral development. This study examines how values education is conceptualized and operationalized within the Türkiye Century Maarif Model (TYMM), a newly introduced national curriculum framework in Türkiye. Using a qualitative document analysis, this research examines official curriculum policy documents published by the Ministry of National Education, focusing on primary education. Data were examined through thematic analysis to identify the structure, scope, and pedagogical orientation of values education embedded in the curriculum. The findings reveal that TYMM positions values not merely as implicit moral principles but as structured learning outcomes integrated into competencies, learning processes, and assessment expectations. The model emphasizes a holistic framework linking virtues, values, and actions, thereby signaling a shift toward more systematic and measurable character education. This study contributes to the literature on curriculum reform and values education by providing an empirically grounded analysis of a national curriculum model. It offers implications for curriculum designers, policymakers, and educators seeking to strengthen values-based education in primary schooling.